Answer:
FD≈25.94.. rounded = 26
Step-by-step explanation:
FD²=12²+(4x+11)²
FD²=144+16x²+88x+121
FD²=265+16x²+88x
also
FD²=12²+(13x-16)²
FD²=144+169x²-416x+256
FD²=400+169x²-416x
thus
265+16x²+88x = 400+169x²-416x
16x²-169x²+88x+416x+265-400 = 0
-153x²+504x-135 = 0
we will solve this quadratic equation by suing the quadratic formula to find x
x=(-504±sqrt(504²-4(-153)(-135)))/2(-153)
x=(-504±
)/2(-153)
x=(-504±
)/-306
x=(-504±
)/-306
x=(-504±414)/-306
x=(-504+414)/-306 and x=(-504-414)/-306
x=-90/-306 and x=-918/-306
x= 5/17 , 3
substituting x by the roots we found
check for 5/17:
4x+11 = 4×(5/17)+11 = (20/17)+11 = (20+187)/17 = 207/17 ≈ 12.17..
13x-16 = 13×(5/17)-16 = (65/17)-16 = (65-272)/17 = -207/17 ≈ -12.17..
check for 3:
4x+11 = 4×3+11 = 12+11 = 23
13x-16 = 13×3-16 = 23
thus 3 is the right root
therfore
ED=23 and CD=23
FD²=FE²+ED² or FD²=FC²+CD²
FD²=12²+23²
FD²=144+529
FD²=673
FD=√673
FD≈25.94.. rounded = 26
Answer:
8
Step-by-step explanation:
hope it help toyou
love
Answer:
(A) Your friend will save $282.
(B) Your friend will get 23.5% off the original price of the mattress.
Step-by-step explanation:
We first need to find out the price of the mattress after the 15% discount. Our first step is to find what 15% of 1,200 is. We can do this by multiplying the two numbers.
1,200 x 15% -----> 1,200 x 0.15= 180.
15% of $1,200 is $180.
Next subtract $180 from $1,200, which equals $1,020. We can now apply the 10% off internet coupon.
1,020 x 10% ------> 1,020 x 0.10= 102.
10% of $1,020 is $102.
Next we subtract $102 from $1,020 and we get $918, the final price of the discounted mattress.
We subtract to see how much money the friend saved.
$1,200 - $918= $282.
We can get the percentage by dividing $282 by $1,200.
282 / 1200= 0.235 decimal form ----> 23.5%
Answer:
the number that you divide by is called the dividend and the number which the dividend is being divided by is the divisor.
Answer:
The linear equation that gives the rule for this table will be:
Step-by-step explanation:
Taking two points from the table
Finding the slope between two points
![\mathrm{Slope}=\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cmathrm%7BSlope%7D%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
![\left(x_1,\:y_1\right)=\left(2,\:27\right),\:\left(x_2,\:y_2\right)=\left(3,\:28\right)](https://tex.z-dn.net/?f=%5Cleft%28x_1%2C%5C%3Ay_1%5Cright%29%3D%5Cleft%282%2C%5C%3A27%5Cright%29%2C%5C%3A%5Cleft%28x_2%2C%5C%3Ay_2%5Cright%29%3D%5Cleft%283%2C%5C%3A28%5Cright%29)
![m=\frac{28-27}{3-2}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B28-27%7D%7B3-2%7D)
![m=1](https://tex.z-dn.net/?f=m%3D1)
We know the slope-intercept form of linear equation is
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
where m is the slope and b is the y-intercept
substituting the point (2, 27) and m=1 in the slope-intercept form to determine the y-intercept 'b'
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
27 = 1(2)+b
27-2 = b
b = 25
Now, substituting m=1 and b=25 in the slope-intercept form to determine the linear equation
y=mx+b
y=1(x)+25
y=x+25
Thus, the linear equation that gives the rule for this table will be: